Differential Economic Opportunity, Transferability of Skills, and Immigration to the United States and Canada - Greenwood, Michael J.; McDowell, John M. (The Review of Economics and Statistics, 1991)
Michael J. Greenwood, John M. McDowell, Differential Economic Opportunity, Transferability of Skills, and Immigration to the United States and Canada, The Review of Economics and Statistics, Vol. 73, No. 4 (Nov., 1991), pp. 612-623